2018
DOI: 10.12944/cwe.13.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Environmental Study on Corn Cob Ash Subjected To Elevated Temperature

Abstract: Rapid increase in greenhouse gas induces mischievous impact on environment. In this study, carbon dioxide emission can be reduced to some extent by replacing some amount of cement with corn cob ash. The performance of concrete at high temperature was also studied. This paper investigates the effect of elevated temperature on strength property of ordinary concretes of grade M25, containing Corn Cob Ash (CCA) at various replacement levels of cement. The cube samples were subjected to high temperature of 1500C, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The optimum blend was obtained at 10% CCA and 90% OPC contents with compressive strength value of 30.17 N/mm 2 . This agrees with the findings of other researchers [35,10] and [36]. This strength gain can be attributed to the cementitious products formed as a result of hydration of cement and those formed when lime reacts with the pozzolana incorporated [37]…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…The optimum blend was obtained at 10% CCA and 90% OPC contents with compressive strength value of 30.17 N/mm 2 . This agrees with the findings of other researchers [35,10] and [36]. This strength gain can be attributed to the cementitious products formed as a result of hydration of cement and those formed when lime reacts with the pozzolana incorporated [37]…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…According to the report of US, China, Brazil, Argentina, and Ukraine have been the leading maize-producing countries in the world and account for about 75.18% of production. Corncob ashes (CCA) have become one of the potential agricultural waste products of pozzolanic materials to be replaced with cement partially [40][41][42][43][44][45]. e test result of the chemical compositions made with X-ray fluorescence (XRF) and energy dispersive X-ray spectroscopy (EDS) conducted by the researchers is shown in Table 3.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Based on the various tests conducted by Singh et al [43], the compressive strength of concrete mixtures made with corncob ashes (CCA) pozzolanic cementitious material decreased with increase in temperature beyond the standard room temperature (20 °C). ey demonstrate laboratory tests to compressive strength for concrete at different elevated temperature (150 °C, 300 °C, 450 °C, and 600 °C) with a CCA content of 5%, 10%, 15%, and 20% to replace cement partially at 0.45 water binder ratio.…”
Section: Effects On Hardening Properties Of Concrete and Mortarmentioning
confidence: 99%
“…• CCA blended cement reduced water absorption. Singh et al (2018) To investigate the impacts of high temperatures on CCA as a replacement for cement in concrete…”
Section: Cca As Cementitious Materialsmentioning
confidence: 99%
“…The authors also demonstrated that the addition of sodium sulfate lowered the setting times, induction times, as well as enhanced the hydration and compressive strength. Singh et al (2018) examined the effect of temperature on the pozzolanic performance and mechanical properties of CCA in concrete. They reported that an increase of CCA content in concrete lowered the compressive strength at normal temperatures; a reverse trend was observed at higher temperatures.…”
Section: References Objective Of the Study Parameters/ Reaction Conditions Findings/conclusionmentioning
confidence: 99%